Patriarchy and Social Norms in Lipstick Under My Burkha - Deyan Rizky Amelia; Nadia Rukyati Hasanah; Sa'diah Nur Rohmah (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2019)
This article discusses the identity of the main characters; Rehana, Leela, and Usha in Lipstick Under My Burkha film released in 2017. The main objectives of this research are to explore how four major characters negotiate the desire of their lives with the patriarchy and social norms that they should obey. This study employs qualitative research method with a cultural approach using the technique of library research. The text is analyzed by using identity theory by Stuart Hall to interpret how women reach their freedom in life. This study not only analyzes the characters of women who wear a burkha but also analyzes all of the four major characters in this film because the main point of this film is about women's dream that cannot be conveyed. The result shows that the four women characters in this film are trying to reach their dream; freedom for woman. Freedom to dress as she wishes refers to Rehana, a freedom to be loved refers to Shireen, freedom to choose a life partner refers to Leela and freedom to do what they want refers to Usha. The attitude and behavior of the four major characters in this film are limited by the patriarchy (manpower) and the social norms. The patriarchy in this film refers to Rehana and Shireen’s life because there are men power represented by the father figure in Rehana’s life and husband figure in Shireen's life. Then,the social norms appear in Leela and Usha’s lifeasboth of them do immoral acts and make them feel ashame.